Ticagrelor or prasugrel in patients with acute coronary syndrome and high bleeding risk. (3rd October 2022) - Lahu, S; Presch, A; Ndrepepa, G; Bernlochner, I; Joner, M; Xhepa, E; Kufner, S; Sager, H B; Mayer, K; Kessler, T; Laugwitz, K L; Schunkert, H; et al.
Abstract: Background: The relative efficacy and safety of more potent P2Y12 inhibitors in patients with acute coronary syndrome (ACS) and high bleeding risk (HBR) undergoing percutaneous coronary intervention (PCI) remains unclear. Purpose: To study the treatment effect of ticagrelor and prasugrel in PCI patients presenting with ACS and HBR. Methods: This post-hoc analysis of the ISAR-REACT 5 trial included patients with ACS undergoing PCI, randomized to ticagrelor or prasugrel, in whom HBR was defined as per Academic Research Consortium criteria. The primary (efficacy) endpoint was the composite of all-cause death, myocardial infarction, or stroke. The secondary (safety) endpoint was Bleeding Academic Research Consortium (BARC) type 3 to 5 bleeding. Outcomes were assessed 12 months after randomisation. Results: Out of the 3, 239 patients included in this analysis, 486 fulfilled the criteria for ARC-HBR definition (HBR group; ticagrelor, n=230 and prasugrel, n=256), whilst 2, 753 did not (non-HBR group; ticagrelor, n=1, 375 and prasugrel, n=1, 378). Compared to the non-HBR group, the HBR group had a higher risk for the primary (hazard ratio [HR]=3.57, 95% confidence interval [CI], 2.79–4.57, p<0.001), and secondary endpoint (HR=2.94 [2.17–3.99], p<0.001). In the HBR group, the primary (HR=1.09; [0.73–1.62]) and secondary (HR=1.18 [0.67–2.08]) endpoints were not statistically different between patients assigned to ticagrelor and prasugrel. In the non-HBR group, the primary endpoint (HR=1.62 [1.19–2.20]) occurred more frequently in patients assigned to ticagrelor as compared to patients assigned to prasugrel, without difference in safety (HR=1.08 [0.74–1.58]). There was no treatment allocation-by-HBR status interaction with respect to the primary (p for interaction = 0.123), or secondary (p for interaction = 0.803) endpoints. Conclusions: In patients with ACS undergoing PCI, HBR status increased both ischemic and bleeding risks without significant impact on the relative efficacy or safety of ticagrelor versus prasugrel. These results warrant confirmation in larger cohorts. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): German Center for Cardiovascular Research (DZHK)Deutsches Herzzentrum München